2013
DOI: 10.1002/asia.201201203
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Privileged Scaffolds by Using Diversity‐Oriented Synthesis

Abstract: An elegant reagent-controlled strategy has been developed for the generation of a diverse range of biologically active scaffolds from a chiral bicyclic lactam. Reduction of the chiral lactam with LAH or alkylation with LHMDS to trigger different cyclization reactions have been shown to generate privileged scaffolds, such as pyrrolidines, indolines, and cyclotryptamines. Their amenability to substitution allows us to create various compound libraries by using these scaffolds. In silico studies were used to esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 117 publications
0
6
0
Order By: Relevance
“…3)22. Preliminary structure activity relationship (SAR) studies indicated that the aromatic or heteroaromatic functionality on the pyrrole moiety played a crucial role in imparting the inhibitory activity.…”
Section: Resultsmentioning
confidence: 99%
“…3)22. Preliminary structure activity relationship (SAR) studies indicated that the aromatic or heteroaromatic functionality on the pyrrole moiety played a crucial role in imparting the inhibitory activity.…”
Section: Resultsmentioning
confidence: 99%
“…They described a reagent-based DOS to afford spirocyclic and fused heterocyclic ring systems. 10,28,29 This strategy afforded biologically relevant molecular scaffolds such as cyclotryptamines, spirooxoindolones, tetrahydroquinolines, spiroindolanes and fused N-heterocycles. 30 The two-step sequence starts with bicy-…”
Section: Doas With Chiral Auxiliariesmentioning
confidence: 99%
“…34 Among the various classes of compounds assayed, particularly interesting were the spiroindolanes, which inhibited cell proliferation of U-937, MCF-7 and HL-60 cell lines at 11-540 nM (with etoposide as control). 10,28 When screened against healthy BHK-1 (baby hamster kidney) cell line, these spiroindolanes required 100 times the concentration of their IC 50 to exhibit any cytotoxicity. The popularity of chiral auxiliaries as templates for DOAS was further exemplified by Sen and co-workers in 2012, via an Evans' chiral oxazolidinone based strategy for the asymmetric synthesis of quinolizidinones, piperizidinones and pyrrolidinones.…”
Section: Doas With Chiral Auxiliariesmentioning
confidence: 99%
See 1 more Smart Citation
“…The compounds thus obtained from the coupling step are again paired with another set of diverse reagents to end up with skeletal, stereochemical, and biologically diverse compounds. This approach has recently been applied to the synthesis of natural product‐inspired compounds [Galloway et al., ] and privileged scaffolds [Evans et al., ; Welsch et al., ; Surakanti et al., ].…”
Section: Designing For Molecular Diversitymentioning
confidence: 99%